Comprehensive Physiology 2018
DOI: 10.1002/cphy.c180006
|View full text |Cite
|
Sign up to set email alerts
|

Motor Neuroprostheses

Abstract: Neuroprostheses (NPs) are electrical stimulators that activate nerves, either to provide sensory input to the central nervous system (sensory NPs), or to activate muscles (motor NPs: MNPs). The first MNPs were belts with inbuilt batteries and electrodes developed in the 1850s to exercise the abdominal muscles. They became enormously popular among the general public, but as a result of exaggerated therapeutic claims they were soon discredited by the medical community. In the 1950s, MNPs reemerged for the seriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 243 publications
0
6
0
Order By: Relevance
“…Transcutaneous systems, which will be the focus of this article, are most frequently used for NMES, FES, and FEST to activate the motor system [ 119 ]. Electrical stimulators create a potential difference between two electrodes, a positive anode and a negative cathode, using surface (transcutaneous) stimulation electrodes [ 118 ].…”
Section: Electrical Stimulation Of Muscles and Nervesmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcutaneous systems, which will be the focus of this article, are most frequently used for NMES, FES, and FEST to activate the motor system [ 119 ]. Electrical stimulators create a potential difference between two electrodes, a positive anode and a negative cathode, using surface (transcutaneous) stimulation electrodes [ 118 ].…”
Section: Electrical Stimulation Of Muscles and Nervesmentioning
confidence: 99%
“…When electrical stimulation is patterned and temporally sequenced to generate coordinated limb movements, this is referred to as functional electrical stimulation (FES). Overall, FES systems fall into the category of motor neuroprostheses [ 119 ], which are devices that use electrical stimulation to activate paralyzed muscles in a functional manner to generate limb movements [ 118 ]. While motor neuroprosthesis could include spinal cord stimulation and deep brain stimulation systems, this review will primarily focus on FES devices for stimulation of muscles and nerves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This form of stimulation is deemed to be adaptive, as it provides direct compensation for the motor disability. In the period since Liberson and colleagues (1961) demonstrated that stimulation delivered to the common peroneal nerve reduced the degree of foot-drop during the swing phase of gait, numerous applications of FES have been developed successfully to assist movement of the upper and lower extremities (Prochazka, 2018). Yet NMES may also be used restoratively, with a view to promoting neural changes that lead ultimately to increased (intrinsic) functional capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Motor neuroprostheses refer to a particular type of neuroprostheses that aim at restoring motor function by electrical stimulation of the structures involved in the generation of movement (muscles, peripheral nerves, spinal cord, or brain), after neuromotor disorders such as stroke or SCI 16 . The very first motor neuroprosthesis was a peroneal nerve stimulator invented in 1961 by Liberson and colleagues to treat foot drop after hemiplegia 17 .…”
Section: Introductionmentioning
confidence: 99%